2014
DOI: 10.1371/journal.pone.0104064
|View full text |Cite
|
Sign up to set email alerts
|

Bordetella Adenylate Cyclase Toxin Differentially Modulates Toll-Like Receptor-Stimulated Activation, Migration and T Cell Stimulatory Capacity of Dendritic Cells

Abstract: Adenylate cyclase toxin (CyaA) is a key virulence factor of the whooping cough agent Bordetella pertussis. The toxin targets CD11b-expressing phagocytes and delivers into their cytosol an adenylyl cyclase (AC) enzyme that subverts cellular signaling by increasing cAMP levels. In the present study, we analyzed the modulatory effects of CyaA on adhesive, migratory and antigen presenting properties of Toll-like receptor (TLR)-activated murine and human dendritic cells (DCs). cAMP signaling of CyaA enhanced TLR-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 59 publications
4
23
0
Order By: Relevance
“…), hence corroborate and validate our previous observations with purified recombinant CyaA. These studies showed that as little as 10 ng/ml of CyaA was able to skew the antigen-presenting capacities of LPS-activated dendritic cells toward a tolerogenic phenotype and made them expand antigen-specific Foxp3 ϩ CD25 ϩ CD4 ϩ Treg cells (54). Higher CyaA concentrations were, indeed, recently found in nasal aspirates of infants with pertussis and in nasopharyngeal washes of B. pertussis-infected baboons (12).…”
Section: Discussionsupporting
confidence: 91%
“…), hence corroborate and validate our previous observations with purified recombinant CyaA. These studies showed that as little as 10 ng/ml of CyaA was able to skew the antigen-presenting capacities of LPS-activated dendritic cells toward a tolerogenic phenotype and made them expand antigen-specific Foxp3 ϩ CD25 ϩ CD4 ϩ Treg cells (54). Higher CyaA concentrations were, indeed, recently found in nasal aspirates of infants with pertussis and in nasopharyngeal washes of B. pertussis-infected baboons (12).…”
Section: Discussionsupporting
confidence: 91%
“…While the immediate outcome of CyaA action appears to consist in ablation of bactericidal functions of sentinel cells of host innate immunity, such as neutrophils and macrophages, action of the CyaA toxin is likely to have also longer lasting subversive effects on adaptive immune response capacities of the host. These would comprise manipulation of dendritic cell maturation and suppression of pro-inflammatory cytokine production, as well as eventual induction of apoptosis of host myeloid phagocytes (CD11b + ) upon prolonged exposure to CyaA in vivo, such as in the lungs of Bordetella pertussis-infected mice (Khelef et al, 1992;Khelef and Guiso, 1995;Boschwitz et al, 1997;Gueirard et al, 1998;Bachelet et al, 2002;Fedele et al, 2010;Adkins et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, phagocytosis and killing of complementopsonized bacteria by neutrophils and macrophages are blocked near-instantaneously (8,11,12). Moreover, CyaA/cAMP signaling also skews the TLR-triggered maturation of dendritic cells and impairs their capacity to present Ags to T cells for induction of adaptive cellular immune responses (13).…”
mentioning
confidence: 99%